Effects of Maharishi Light Technology with Gems: A random-assignment, placebo-controlled, blinded pilot study. (May 2020) - Travis, Frederick; Melzer, Ayala; Scharf, David
Objectives: This blinded random-assignment, placebo-controlled pilot study investigated the effects of Maharishi Light Technology with Gems on three self-report measures: a questionnaire with a 5-point Likert-type scale, the Profile of Mood States (POMS), and an open-ended question. This pilot is the beginning of a research program to test the effects of this therapy. Methods: In total, 18 meditating subjects received two treatments on consecutive days, randomly either Maharishi Light Technology or placebo, then 2 weeks rest, and then the other treatment on consecutive days. Results: In comparison to placebo treatments, Maharishi Light Technology treatments were (1) rated as being significantly more settled, (2) higher on the Positive Self-Esteem subscale of the POMS and (3) described by the terms: healing, wholeness, and bliss. Conclusion: These treatments lead to significant improvements on self-report measures. Future research could assess their effects across both meditating and nonmeditating populations, using physiological measures to probe possible mechanisms of the effects.